In vitro Antimicrobial and in vivo Lead Acetate Poison Abatement Study of Garcinia kola Heckel. Issue 6 (1st November 2017) - Osemwegie, Omorefosa Osarenkhoe; Nwonuma, Charles Obiora; Oluyori, Abimbola Peter; Abraham, Praise Ocheanya; Akanbi, Abraham Abayomi; Opaleke, Deborah Oluyemisi; Alejolowo, Omokolade Oluwaseyi
Abstract: The in vitro antimicrobial and in vivo heavy metal abatement properties of aqueous extracts of Garcinia kola Heckel (bitter cola) were investigated using opportunistic pathogens and Wistar rats as experimental models. A marked inhibitory activity against Aspergillus niger, Aspergillus flavus and Candida albicans was recorded at 100 mg/ml of the crude relative to ketoconozole and fluconazole drugs. Similarly, different concentrations (25 mg/ml, 50 mg/ml and 100 mg/ml) of the crude extracts of bitter cola inhibited species of Escherichia coli and Pseudomonas aeruginosa almost as effectively as the control drug of streptomycine used. Chronic lead acetate poisoned wistar rats in groups B, C, D, E exposed to G. kola supplemented feed and water ad libitum showed variable decrease in the serum alkaline phosphatase level while aspartate and alanine aminotransferases level reduces in C and D groups compared to the negative control group. The kidney biomarkers; serum creatinine and urea concentrations were not significantly different at P ≤ 0.05 for rat groups C, D, E when compared with the positive and negative control groups respectively. Mild infiltration and cell distortion were observed in the liver and kidney sections of the rats exposed to uncoated bitter cola supplemented feed while suggesting an overriding effect from the nut coats. The study reaffirms the medicinal potential of coated and uncoated bitter cola to act as abatement of lead toxicity and alternative antimicrobial. Furthermore, G. kola could be a double-edged drug for the spontaneous amelioration of lead toxicity and secondary infections due to lead poisoning.